Effects of Retting Media Circulation and Temperature on the Fermentation Process in Soft-Texture and Low Cyanogenic Content Cassava Flour Production - M.T.A.P. Kresnowati; Yazid Bindar; Lienda Aliwarga; Dianika Lestari; Nicholaus Prasetya; A. R. Tanujaya (ASEAN Journal of Chemical Engineering, 2015)
A fermentation process to produce soft-texture and low cyanogenic content cassava flour had been studied, in particular the effects of temperature, circulation of the retting media, and scale to the reduction of cyanogenic content and the structure of cassava. Although the effects of retting media circulation and an increase in the fermentation temperature on cyanogenic content reduction were not clearly seen, they led to more damaged cassava structure and thus improving the overall cassava flour production. On the other hand small scale fermentation led to both cyanogenic content reduction and morphological changes, giving better fermentation performance.